Words by heart - Sebestyen, Ouida (Boston : Little, Brown, 1979)
A young black girl struggles to fulfill her papa's dream of a better future for their family in the southwestern town where, in 1910, they are the only blacks.
"An Atlantic Monthly Press book."
Keywords: Fathers and daughters -- Fiction; Race relations -- Fiction